2021
DOI: 10.12788/jhm.3717
|View full text |Cite
|
Sign up to set email alerts
|

Association of Healthcare Access With Intensive Care Unit Utilization and Mortality in Patients of Hispanic Ethnicity Hospitalized With COVID‐19

Abstract: BACKGROUND: Racial and ethnic minority groups in the United States experience a disproportionate burden of COVID-19 deaths. OBJECTIVE: To evaluate whether outcome differences between Hispanic and non-Hispanic COVID-19 hospitalized patients exist and, if so, to identify the main malleable contributing factors. DESIGN, SETTING, PARTICIPANTS: Retrospective, cross-sectional, observational study of 6097 adult COVID-19 patients hospitalized within a single large healthcare system from March to November 2020. EXPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…First, although we did not find statistically significant differences in care escalation from AH-HaH to brick-and-mortar facilities for Hispanic vs. non-Hispanic White patients, other studies of patients hospitalized in traditional care settings indicate that Hispanics have been disproportionately impacted by poor COVID-19 outcomes [ 9 , 10 , 23 ]. Similar studies have shown that Hispanic patients have higher rates of hospitalization, severe disease requiring intensive care, intubation, and mortality [ 24 27 ].…”
Section: Discussionmentioning
confidence: 83%
“…First, although we did not find statistically significant differences in care escalation from AH-HaH to brick-and-mortar facilities for Hispanic vs. non-Hispanic White patients, other studies of patients hospitalized in traditional care settings indicate that Hispanics have been disproportionately impacted by poor COVID-19 outcomes [ 9 , 10 , 23 ]. Similar studies have shown that Hispanic patients have higher rates of hospitalization, severe disease requiring intensive care, intubation, and mortality [ 24 27 ].…”
Section: Discussionmentioning
confidence: 83%
“…For example, African American patients have the highest disease burden requiring intensive care treatments and are more likely to die from sepsis. During the COVID-19 pandemic, Hispanic patients have been found to have higher ICU utilization and mortality than non-Hispanic patients [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors declare no conflict of interest. Suchita S. Sata MD 1,2 S. Ryan Greysen MD, MHS Email: Suchita.shah.sata@duke.edu; Twitter: @SuchitaSata ORCID Suchita S. Sata http://orcid.org/0000-0002-9773-6174…”
Section: Conflict Of Interestmentioning
confidence: 99%